Performance of phthaloylchitosan as a host for ionic conduction / Nurzila Abdul Aziz - Nurzila, Abdul Aziz (2017)
Phthaloylchitosan (Phch) has been synthesized by reacting excess phthalic anhydride with chitosan in the presence of nitrogen gas (N2). The of phthaloylchitosan structure has been confirmed by Fourier-transform infrared (FTIR) spectroscopy. Bands at 1773 cm−1 and 1713 cm−1 attributable to the pthalimido group are observed. X-ray diffraction (XRD) shows that the samples are largely amorphous. Thermal stability of chitosan is increased on phthaloylation. Ammonium thiocyanate (NH4SCN), ammonium triflate (NH4CF3SO3) and ammonium Iodide (NH4I), have been added to the solution of phthaloyl chitosan in N,N-Dimethylformamide (DMF) before casting to form films. The amount of salts added ranges from 5 to 50 wt. % concentration. The significant bands at 1773 cm-1 and 1703 cm-1 for the phthalimido group show wavenumber shifts for all samples proving that complexation has taken place. The highest conductivity at 298 K is 2.42×10−5 S cm−1 for sample 70 wt. % Phch-30 wt. % NH4SCN, 1.25×10−4 S cm−1 for sample 60 wt. % Phch-40 wt. % NH4I and 6.01×10-4 S cm−1 for sample 50 wt. % Phch- 50 wt. % NH4CF3SO3. The conductivity-temperature relationship seems to obey the Vogel-Tamman-Fulcher (VTF) rule between 298 K and 373 K. The frequency range for impedance spectroscopy was from 0.1 Hz to 1×107 Hz. The lowest pseudo activation energy, ‘B’ is associated with the highest conducting sample. Relaxation peaks are observed from dielectric loss and tangent delta variation with frequency at ambient and elevated temperatures in the frequency range investigated. From linear sweep voltammetry (LSV) analysis, decomposition voltage are 2.1 V, 1.8 V and 2.1 V for system 70 wt. % Phch-30 wt. % NH4SCN, 60 wt. % Phch-40 wt. % NH4I and 50 wt. % Phch-50 wt. % NH4CF3SO3 respectively. The transference number measurements show that the highest conducting samples are ionic conductors. The samples 70 wt. % Phch- 30 wt. % NH4SCN and 50 wt. % Phch-50 wt. % NH4CF3SO3 have been used to fabricate electrochemical double layer capacitor (EDLC). The calculated specific capacitance for the EDLC with 70 wt. % Phch-30 wt. % NH4SCN electrolyte is 16 Fg-1 while the EDLC with 50 wt. % Phch-50 wt. % NH4CF3SO3 is 27 F g-1 at 5 mVs-1 scan rates. The sample 60 wt. % Phch-40 wt. % NH4I electrolyte has been used to fabricate a dye sensitized solar cell (DSSC) using natural dye. The short-circuit current density, Jsc and open-circuit voltage, OCV obtained from the cell employing the 60 wt. % Phch-40 wt. % NH4I electrolyte under white light illumination of intensity 56.4 mW cm−2 are 681 μA cm−2 and 0.4 V respectively. The fill factor FF and efficiency η obtained from this study are 0.41 and 1.98% respectively.